The exploration of Durban consumer perceptions and preferences of selected fast food chicken brands - Prinsloo, Steven (The IIE, 2018)
This small-scale qualitative study studied the concept of international versus local/home-grown fast food chicken outlets by exploring the preferences and perceptions of millennial consumers around selected fast food chicken brands. The research specifically focuses on the fast food chicken brands Afros, Nandos and KFC within the fast food chicken market in Durban. The study reviews themes and theories that are relevant to millennial consumers, fast food and branding of fast food chicken stores with brand equity and its various elements. The study collected data from a small sample group who represented the population of millennial fast food chicken consumers within the Durban area. The study utilized a qualitative approach which allowed for more in-depth and insightful findings throughout the primary research. The research methods used to collect and analyse primary data were focus groups and in-depth interviews. The insights found in the study led to findings and recommendations that could provide value to local fast food brands to improve on their products, service and branding. It was concluded that while local fast food stores are attracting consumers for their quality food, healthiness and positive and relatable store atmosphere, they are not able to compete with international fast food restaurants due factors such as price, variety and convenience.
Keywords: Fast food brands; Millennials; Consumer behaviour